New Urbanism as Sustainable Development?. Issue 6 (25th June 2013) - Trudeau, Dan
Abstract New urbanism is an urban design movement to create pedestrian‐oriented settlements that also advance social equity and mitigate the environmental impacts of development. Proponents of the movement have suggested it offers a model of sustainable development. This paper investigates this claim by discussing the implications of empirical research on new urbanism for the ways in which the movement contributes to sustainability. The paper uses the concepts of environmental and social sustainability to frame the discussion. The paper traces the origin of new urbanism and the evolution of its interest in sustainable development. Review of scholarly research on new urbanism in practice shows the movement supports in limited ways both environmental and social sustainability. Moreover, this research also shows that some forms of new urbanism development unintentionally counteract environmental sustainability goals while other forms fail to achieve social sustainability goals. Citing the diverse ways in which new urbanism is put into practice, the paper concludes by considering how understanding the heterogeneity of new urbanism as it exists in the world will impart greater clarity to further analysis of the ways in which the movement actually contributes to sustainable development.